THE SEPARATION OF POWERS AND PRINCIPLES OF STATE POLICY - Tomy Michael (International Journal of Law in Changing World, 2025)
This article examines the main points of state policy, which is more popularly known as the Outlines of State Policy (GBHN), but in fact, the two meanings are very different. Referring to the Decree of the People’s Consultative Assembly of the Republic of Indonesia Number IV/MPR/2014 concerning the Recommendation of the People’s Consultative Assembly of the Republic of Indonesia for the 2009-2014 Term of Office, specifically in Point 10 it is written to reformulate the national development planning system with the GBHN as model. Although the GBHN was rejected, it became a reference. Before the reform, the GBHN in state administration made the People’s Consultative Assembly (MPR) the highest state institution. After the reform, it tends to follow the theory of separation of powers as the highest center for carrying out national life. This article employs Hans-Georg Gadamer’s hermeneutical interpretation method. The principles of state policy must be understood in the context of the separation of powers, as this determines the application of power. This separation continues on the principle of sharing and checking. Separation of powers is not synonymous with democracy, but it is the origin of the state, allowing the formation of power to continue the state’s existence. _____ LA SEPARACIÓN DE PODERES Y LOS PRINCIPIOS DE LA POLÍTICA DE ESTADO Este artículo examina los puntos principales de la política de estado, conocida popularmente como los Lineamientos de la Política de Estado (LPE), aunque en realidad sus significados son muy diferentes. En referencia al Decreto de la Asamblea Consultiva Popular de la República de Indonesia número IV/MPR/2014 sobre la Recomendación de la Asamblea Consultiva Popular de la República de Indonesia para el período 2009-2014, en su punto 10 se propone reformular el sistema nacional de planificación del desarrollo tomando como modelo los LPE. Si bien fueron rechazados, se convirtieron en una referencia. Antes de la reforma, los LPE en la administración estatal convertían a la Asamblea Consultiva Popular (ACP) en la máxima institución estatal. Tras la reforma, tienden a seguir la teoría de la separación de poderes como el centro supremo para la vida nacional. Este artículo emplea el método de interpretación hermenéutica de Hans-Georg Gadamer. Los principios de la política de Estado deben entenderse en el contexto de la separación de poderes, ya que esta determina su aplicación. Esta separación se basa en el principio de reparto y control. La separación de poderes no es sinónimo de democracia, pero es el origen del Estado, permitiendo la formación del poder para la continuidad de su existencia. _____ 权力分立与国家政策原则 本文探讨国家政策的要点，即更通俗的说法——国家政策大纲（GBHN），但实际上，两者含义截然不同。参考印度尼西亚共和国人民协商会议第IV/MPR/2014号法令《关于印度尼西亚共和国人民协商会议2009-2014年任期建议》，其中第10点明确提出以GBHN为范本，重新制定国家发展规划体系。GBHN虽然被否决，但却成为一种参考。改革前，国家行政管理中的GBHN将人民协商会议（MPR）确立为最高国家机构。改革后，GBHN更倾向于遵循权力分立理论，将其作为开展国家生活的最高中心。本文运用汉斯-格奥尔格·伽达默尔的诠释学解释方法。国家政策的原则必须在权力分立的背景下理解，因为这决定了权力的运用。这种分立遵循分享与制约的原则。权力分立并非民主的同义词，但它是国家的起源，它使权力的形成得以延续，从而延续国家的存在。